Ichneumonidae species (Hymenoptera) new to Iraq recorded from Kurdistan - Srwa Hamad (Biodiversity Data Journal, 2025)
Ichneumonidae, a dominant and ecologically important family of parasitoids in the large insect order Hymenoptera, are poorly studied in Iraq, with only 18 previously recorded and identified species known so far. During a survey in Kurdistan, Iraq, numerous Ichneumonidae species were collected in July 2023 using a Malaise trap.Fourteen species of Hymenoptera: Ichneumonidae are herein newly recorded for the fauna of Iraq: Phaenolobus hilalii Kolarov & Gürbüz, 2010; Lissonota deversor Gravenhorst, 1829; Alcima orbitale (Gravenhorst, 1829); Campoletis scyticus Riedel, 2017; Casinaria tenuiventris (Gravenhorst, 1829); Cryptus spinosus Gravenhorst, 1829; Perilissus dissimilator Aubert, 1987; Diadromus collaris (Gravenhorst, 1829); Clistopyga incitator (Fabricius, 1793); Itoplectis tunetana (Schmiedeknecht, 1914); Pimpla flavicoxis Thomson, 1877; Pimpla spuria Gravenhorst, 1829; Zaglyptus multicolor (Gravenhorst, 1829) and Zatypota bohemani (Holmgren, 1860). Recorded distributions are provided for all species, summarised for very widely distributed species.